Uji Efektivitas Jus Buah Naga Merah (Hylocereus polyrhizus) dalam Meningkatkan Hemoglobin pada Karyawan RS Sri Pamela - Sabnita, Rara; Suharsih, Suharsih (Mahesa Research Center, 2025)
Anemia is a common health issue frequently experienced by individuals in the productive age group, including healthcare workers, and is generally caused by iron deficiency. Red dragon fruit (Hylocereus polyrhizus) is known to contain iron and vitamin C, which may help increase hemoglobin levels. This study aimed to determine the effect of red dragon fruit juice on the hemoglobin levels of employees at Sri Pamela Hospital, Tebing Tinggi. A pre-experimental design with a one-group pretest-posttest approach was used involving 30 respondents (10 males and 20 females) who consumed 200 mL of red dragon fruit juice daily for 10 consecutive days. Hemoglobin levels were measured before and after the intervention using the Drabkin method and an automated hematology analyzer. Statistical analysis using a paired sample t-test showed a significant increase in hemoglobin levels, both in male (14.99 to 16.33 g/dL) and female (13.51 to 15.35 g/dL) participants, with a p-value of 0.000. In conclusion, red dragon fruit juice effectively increases hemoglobin levels and has potential as a natural nutritional intervention for the prevention of mild anemia.